Investigating the structural and cultural conditions that reproduce coloniality and inhibit decolonisation at a private higher education institution in South Africa - Leburu, Mosuwa Nemeya Prince (School of Education, 2025)
This qualitative research study seeking to establish the structural and systemic inhibitors of decolonisation at a South African Private Higher Education Institution (PHEI), adopted a Critical and Social Realism theoretical framework while employing a critical discourse analytical approach. Working within an interpretive paradigm, the study gathered data through semi-structured interviews involving the PHEI lecturers whose agential association purposively placed them at vantage points to assess the structural and cultural elements that stunt the progression of transformation. The study established that the absence of institutional commitment to decolonisation informed the lecturers' peripheral influence in executing a decolonisation agenda. It was also established that the lecturers' perceptions of decolonisation did not progress beyond intellectual and academic pronouncements and as such, institutional structure and culture continue to inhibit decolonisation. That lack of depth on the part of lecturers compromised their competence to pronounce on apparent structural and racial configurations manifest in the institution. The study recommended further investigations that would triangulate the experiences of multiple stakeholders in a bid to propose a framework that would foreground decolonisation and curriculum change as a central concern.